A Randomized, Controlled, Multicenter Study of Technology‐Based Weight Loss Interventions among Endometrial Cancer Survivors. (31st October 2017) - Haggerty, Ashley F.; Hagemann, Andrea; Barnett, Matthew; Thornquist, Mark; Neuhouser, Marian L.; Horowitz, Neil; Colditz, Graham A.; Sarwer, David B.; Ko, Emily M.; Allison, Kelly C.
Abstract : Objective: The aim of this study was to test the efficacy of technology‐based weight loss interventions for endometrial cancer (EC) survivors with obesity. Methods: EC survivors with obesity ( n  = 196) from three medical centers completed assessments for knowledge of obesity as a risk for EC and interest in weight management. Forty‐one women were randomized to a 6‐month intervention: telemedicine with Wi‐Fi scales, text messaging (texting), or enhanced usual care (EUC). Changes in anthropometrics and psychosocial measures were analyzed. Results: One‐third of survey participants lacked awareness that obesity increased the risk of EC, and 40% misclassified their body mass. There were no significant differences in weight loss across interventions (mean = −4.4 kg, SD = 6.5 kg). Telemedicine showed improvements in physical health and cancer‐related body image ( P s = 0.04) compared to texting and in sexual functioning compared to EUC ( P  = 0.03). Total physical activity was increased in EUC compared with telemedicine (P =  0.01), and vigorous physical activity was increased in EUC compared with both interventions ( P  = 0.01‐0.03); walking significantly increased in texting compared with telemedicine ( P  = 0.02). Conclusions: Technology‐based lifestyle interventions in EC survivors with obesity were accessible and resulted in weight loss and improved quality of life. EUC also produced weight loss, demonstrating a potential for beginning weight management with information on specific diet and exercise goals.